Prinsip Kepastian Hukum Organisasi Advokat dalam Rangka Perlindungan Hukum Bagi Pengguna Jasa Advokat - Heqqy Rioscar Bramanta; I Gede Widhiana Suarda; Moh. Ali (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
During the 2015 PERADI National Conference (Munas) in Makassar, PERADI was divided into three management sections, namely Fauzie Yusuf Hasibuan's PerADI, Luhut MP Pangaribuan's PerADI, and PADI's Peradi. PERADI version Juniver Girsang and later could not give birth to the management received by all circles. Chief Justice of the Supreme Court R.I. Number 073/KMA/HK.01/XI/2015\. This has an impact on advocates establishing organizations in accordance with their respective philosophies and ideals. The type of research in this study is a juridical review that regulates the use of regulations or standards in specific regulations. Studies show that Law No. 18 of 2003 on Advocates provides protection for clients, including by ensuring confidentiality of advocate and client relationships, granting immunity rights to advocates, ensuring protection of attorney files and documents. ensuring protection against wiretapping of advocate electronic communications, ensuring protection of advocate's right to obtain information, data, and documents necessary for defense of client interests, Advocates who do not exercise their obligations to fulfill the rights of their clients or are found to have committed unlawful acts will be sanctioned by the advocate organization or the Advocate Honorary Council, and the concept of single bar with Peradi as the only advocate organization is an ideal form of the advocate organization model in Indonesia.